ChemInform Abstract: DNA Functionalized Fluorescent Quantum Dots for Bioanalytical Applications. Issue 21 (6th May 2016) - Zhang, Cuiling; Ding, Caiping; Xiang, Dongshan; Li, Li; Ji, Xinghu; He, Zhike; Xian, Yuezhong
Abstract: Review: 105 refs.